Serbia’s New Growth Agenda : Investment for Growth - World Bank (World Bank, Washington, DC, 2020)
Because of its difficult starting position in transitioning to a market economy, so far macroeconomic policy in Serbia has mainly been concerned with achieving stability. At the start of its transition in 2001, Serbia was practically bankrupt, burdened with old overdue debt and huge arrears in budgetary payments, especially pensions. At the end of 2000, public debt was 175 percent of GDP and external debt was 128 percent. In both 2000 and 2001, inflation was over 80 percent. High inflation and external imbalances were the main concerns all the way through the global financial crisis (GFC). The GFC (as well as external shocks) brought multiple recessions between 2009 and 2014, and a major widening of the fiscal deficit. Since 2014, the focus has been on consolidating public finances, in addition to keeping inflation low. While macroeconomic stability is a necessary precondition for growth, the question is whether Serbia can do more to create a pro-growth environment. Serbia has succeeded in keeping inflation low over recent years; the current account deficit (CAD) is now low enough to be manageable and is almost entirely financed by non-debt-creating flows; large fiscal deficits have been converted to a surplus; and public debt is heading downward. However, growth is still meager. To ensure that the Serbian economy grows more quickly, the focus should be on increasing investment—both private and public.